A prospective randomized trial comparing Restorelle® Y mesh and flat mesh for laparoscopic and robotic-assisted laparoscopic sacrocolpopexy: 24-month outcomes - Ferrando, Cecile A.; Paraiso, Marie Fidela R. (International Urogynecology Journal, 2021)
Objective To compare prolapse recurrence and the incidence of mesh exposure between Restorelle® Y mesh and dual flat mesh. Methods A randomized trial of women undergoing laparoscopic (LSC) or robotic (RSC) sacrocolpopexy for post-hysterectomy vaginal prolapse. Subjects were randomized to either Y mesh or dual flat mesh. Subjects underwent a pelvic examination with POP-Q and evaluation of any mesh exposure, and the PFDI-20 was administered at 6, 12 and 24 months postoperatively. Subjective recurrence was defined by symptomatic vaginal bulge. All subjects underwent pelvic examination with POP-Q at 6, 12 and 24 months. Objective recurrence was defined by descent of the apex > 1/3 into the vaginal canal, anterior or posterior vaginal descent beyond the hymen, or retreatment for prolapse. Results Sixty-two patients were enrolled, and 59 patients were implanted with mesh: 30 Y mesh (17 LSC, 13 RSC) and 29 flat mesh (18 LSC, 11 RSC). There were no differences in patient characteristics between the groups. At 24 months, data were available for 44 (74.5%) patients. There were no mesh exposures for all subjects. PFDI-20 scores improved significantly for all subjects with no differences in mean improvement by mesh configuration. There were no differences in subjective and objective recurrence rates between the groups. Four patients (9.1%) complained of subjective vaginal bulge symptoms while nine (20.5%) patients had an objective recurrence (77.8% [7] examination only and 22.2% [2] reoperation). There were no apical recurrences. Of those patients who had a recurrence on examination only ( n = 7), 85.7% (6) were asymptomatic. Conclusions At 24 months, there were no differences in subjective outcomes and prolapse recurrence in patients who underwent sacrocolpopexy with the Restorelle® Y mesh versus dual flat mesh. One in five patients experienced an objective recurrence; however, there were no apical recurrences and the majority were asymptomatic.